Pengaruh Kompensasi, Disiplin Kerja, Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada Pos Kota Jakarta - mas wahyu wibowo (Jurnal Ilmiah Manajemen dan Bisnis, 2019)
The purpose of this study is to analyze the influence of compensation, work discipline and physical work environment on employee performance in the Pos Kota Office Jakarta on 2017th. The result of the research by using primary data in the form of questionnaires to 102 employees in Pos Kota Office Jakarta with Probability Sampling (Simple Random Sampling) method. shows that the compensation, work discipline, and physical work environment showing a positive and significant impact on employee performance. There is a positive and significant influence between compensation, work discipline, and physical work environment seen from the analysis of comparative linear regression calculation has a regression coefficient of 0.273, the work discipline has a regression coefficient of 0.304 and the physical work environment has a regression coefficient of 0.403, it indicates that compensation , work discipline and a good physical work environment will improve the performance of  Pos Kota Employee. The results shows that the compensation, work discipline, and physical work environment that has been given by Pos Kota Office has done well in accordance with their respective objectives and can be responded well by the employee. High performance of Pos Kota employee indicates that Pos Kota Office is able to control the work performance of Pos Kota employee based on the benefits received so Pos Kota employee are able to do the job according to their respective responsibilities